Profitability and Efficiency Analysis to Measure the Impact of Fintech on The Financial Performance of Regional Development Banks - Pardede, Vivaldi Wijaya; Champaca, Mychelia (Fakultas Ekonomi dan Bisnis Universitas Brawijaya, 2025)
The development of digital technology has driven significant transformation in the financial industry, especially with the emergence of financial technology (fintech) companies that have become serious competitors for conventional financial institutions. In Indonesia, online lending-based fintech is increasingly in demand, posing challenges to the profitability and efficiency of banks, including Regional Development Banks (BPD). This study aims to determine the differences in BPD financial performance before and during the presence of fintech, in terms of the Return on Asset (ROA), Return on Equity (ROE), Net Interest Margin (NIM), and Operating Expenses to Operating Income (BOPO) ratios. This study uses a comparative quantitative approach with a sample of 7 BPDs selected through area sampling techniques from a total population of 24 conventional BPDs. Data were taken from financial reports for the periods 2013–2016 (before fintech) and 2017–2020 (during fintech). The analysis was carried out using the Wilcoxon Signed Rank Test with the help of STATA software, because the data was not normally distributed. The results showed that ROA, ROE, and NIM experienced significant differences between the two periods, while BOPO did not show any significant differences. This finding indicates that the presence of fintech has an impact on profitability, but not on operational efficiency. This study provides an empirical contribution in seeing the impact of fintech on the financial performance of regional banks and can be a basis for regulators and management in formulating financial technology adaptation strategies in the future.